Policy and regulatory changes for a successful startup revolution: Experiences from the startup action plan in India - Vijay Kumar Singh (Asian Development Bank Institute (ADBI), 2020)
In January 2016, the Government of India launched the Startup India initiative, which has transformed the way in which the markets, potential entrepreneurs, and investors view startups. This transformation included a slew of policy measures intended to promote a startup culture and allow younger population members to take risk with their ideas and become "job creators" rather than "job seekers." India's demographic dividend required a suitable channelization of human resources. The Startup Action Plan (SAP) of 2016 proposed to address three key areas for empowering potential startups: (i) handholding and simplification; (ii) funding support and incentives; and (iii) incubation and industry-academia partnership. Emerging as the third-largest startup ecosystem of the world, India has potential for enormous growth. There have been several policies at all levels of government, industry, and academia to promote a startup culture. However, it is important to examine these initiatives and determine whether they move beyond the subsidy/tax holiday mindset and work on the root corrections necessary for a robust startup ecosystem. There are several issues that require consideration from the policy and regulatory perspective for a successful startup revolution. This paper explores these initiatives that the Government of India has taken and identifies the gaps that require attention from stakeholders. The paper also investigates the major challenges and potential solutions arising from the Indian experience of initiatives in the startup revolution.
Keywords: K29; K22; M13; L26; O31; J23; K15; K22; K29; 330; startup; legal compliance; financing; investors; global partnerships; entrepreneurship; incubation